Strategies To Prevent Home-Grown Terrorism In Ghana - Zulkarnain, Mohammed (2018)
In the wake of the September 11, 2001 attacks, home-grown terrorism (HGT) emerged with significant threat to all nations across Europe, America, Asia and Africa. In recent years, HGT has caused the death of many people and is gravely threatening humanity across the world, affecting human security, well-being and peaceful state of many individuals living in both developed and developing nations. Therefore, this study explored the nature of HGT in Ghana by assessing the strategies used by state and non-state actors to counter it by adopting the Human Security frameworks to understand the strategies adopted by Ghana to prevent HGT in an unstable West African region, where countries like: Ivory Coast, Burkina Faso, Niger, Mali and Nigeria, have all suffered from HGT.